Plant nuclear structure, genome architecture, and gene regulation - Evans, D. E. (David E.) (Chichester, West Sussex, UK ; Hoboken, New Jersey : Wiley-Blackwell, 2013)
"Brings together expert reviews of the recent significant advances in our knowledge and understanding of the organisation of the higher plant nucleus, and in particular in the relationship between nuclear organisation and the regulation of gene expression. Rapid progress has been made in a number of key areas over the last five years, including description and characterization of proteins of the nuclear envelope and nuclear pore complex, novel insights into nucleoskeletal structures, as well as developments related to chromatin organization, function and gene expression. These advances open the way for new research into areas such as stress tolerance, plant-pathogen interactions and ultimately crop improvement and food security. Continued research into plant nuclear structure, genome architecture and gene regulation also enriches our understanding of the origin and evolution of the nucleus and its envelope."--Publisher's book description.
3.3 The Dynamics of the Nuclear Pore Complex3.3.1 Types of mitosis; 3.3.2 NPC disassembly and dynamics of animal NPC components; 3.3.3 Dynamics of fungal NPC components; 3.3.4 Dynamics of plant NPC components; 3.4 Conclusions; References; 4 Nucleoskeleton in Plants: The Functional Organization of Filaments in the Nucleus; 4.1 Introduction; 4.2 Intermediate filaments and the nucleoskeleton; 4.3 Plants do not have intermediate filaments but they may have functional equivalents; 4.4 Plants can evolve different solutions to the same problem; 4.5 Intermediate filaments first evolved in the nucleus.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Keywords: Plant gene expression; Plant genomes; Genome, Plant; Plant genomes -- Research -- Methodology; Plant genomes; Plant molecular genetics; SCIENCE -- Life Sciences -- Genetics & Genomics; Plant gene expression; Plant genomes; Electronic books